Answers

2014-06-18T10:04:05+08:00
Cube of a binomial: (a+b)³ = (a+b)(a+b)(a+b)
                                       MULTIPLY USING DISTRIBUTIVE PROPERTY
                                      = (a² + 2ab + b²)(a+b)
                                      = a³ + 2a²b + ab² + a²b + 2ab² + b³
                                        COMBINE SIMILAR TERMS
                            (a+b)³ = a³ + 3a²b + 3ab² + b³
From the given: (7 +c )³

we let:
                             a = 7
                             b = c
Then substitute to the final equation:

                            (7 + c)³ = (7)³ + (3)(7²)(c) + (3)(7)(c²) + (c³)
                                        = 343 + 147c + 21c² + c³
                                        = c³ + 21c² + 147c + 343 ANSWER...
0